Self-assembly pattern directed sustained release from porous microspheres of discotic tripeptides. Issue 9 (26th November 2020) - Kumar, Santosh; Bera, Santu; Nandi, Sujay Kumar; Haldar, Debasish
Abstract : The round clay pitcher-like porous microspheres of the C 2 -symmetric discotic tripeptide are more efficient than the bird nest-like porous microspheres of the C 3 -symmetric discotic tripeptide, for the sustained release of drugs. Abstract : Porous microspheres from discotic tripeptides have been investigated as potential candidates for drug delivery vehicles. The C 3 symmetric discotic tripeptide adopts a supramolecular helical column structure by three fold intermolecular hydrogen bonding interactions as well as face to face π–π stacking interactions. But the C 2 symmetric discotic tripeptide adopts a supramolecular dimer like structure by six-fold intermolecular hydrogen bonding interactions and face to face π–π stacking interactions. Field emission scanning electron microscopy (FE-SEM) revealed that the C 3 symmetric discotic tripeptide exhibits bird nest-like porous microsphere morphology formed by the assembly of the individual columns. However the C 2 symmetric discotic tripeptide forms round clay pitcher like porous microspheres. These porous microspheres have been used as potential carriers for the sustained release of a bacteriostatic antibiotic sulfamethoxazole. The spectroscopic studies as well as the growth inhibition of E. coli reveal that the round clay pitcher-like porous microspheres are more efficient than the bird nest-like porous microspheres for the sustained release of drugs. The report highlights the importance of the self-assembly pattern for the fabrication of advanced functional materials.